2020
DOI: 10.1021/acs.jafc.0c00784
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Astaxanthin: PEGylated Astaxanthin Fights Diabetes by Enhancing the Solubility and Oral Absorbability

Abstract: To develop hydrophilic astaxanthin with significantly enhanced solubility and stability, astaxanthin polyethylene glycol succinate (APGS) was synthesized by esterification of an astaxanthin succinate diester with polyethylene glycol 1000. The chemical structure of the hydrophilic derivative was confirmed by 1H nuclear magnetic resonance and mass spectra. APGS showed better solubility than free astaxanthin in water and enhanced bioavailability compared to that of free astaxanthin. Additionally, testing the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Further, the administration of AOD reversed HFD-induced oxidative stress injury and inflammation, as supported by the reduced MDA level and the expression levels of inflammatory cytokines (e.g., TNF-α, IL-1β, and IFN-γ). Similar antidiabetic and anti-inflammatory effects were found in astaxanthin polyethylene glycol succinate conjugates, which is a synthetic hydrophilic astaxanthin with significantly enhanced solubility and stability compared with AST [25]. Further study was conducted around gut microbiota in our research.…”
Section: Discussionsupporting
confidence: 59%
“…Further, the administration of AOD reversed HFD-induced oxidative stress injury and inflammation, as supported by the reduced MDA level and the expression levels of inflammatory cytokines (e.g., TNF-α, IL-1β, and IFN-γ). Similar antidiabetic and anti-inflammatory effects were found in astaxanthin polyethylene glycol succinate conjugates, which is a synthetic hydrophilic astaxanthin with significantly enhanced solubility and stability compared with AST [25]. Further study was conducted around gut microbiota in our research.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, astaxanthin could suppress the activation of the NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome in macrophages (Peng et al, 2020). Moreover, multiple in vivo studies have revealed the anti-inflammatory effects of astaxanthin in different disease models, including non-alcoholic fatty liver (Bhuvaneswari et al, 2014;Ni et al, 2015;Chiu et al, 2016;Jia et al, 2016), hepatic injury or fibrosis Han et al, 2018;Liu et al, 2018;Zhang Z. et al, 2020), kidney injury (Guo et al, 2021), myocardial injury (Xie et al, 2020), diabetes mellitus (Feng et al, 2020;Liu et al, 2020;Zhuge et al, 2021), arthritis (Park MH. et al, 2020;Kumar et al, 2020), gastroenteritis inflammation (Han et al, 2020;Chen Y. et al, 2021), acute pancreatitis (Yasui et al, 2011), asthma (Hwang et al, 2017), atopic dermatitis (Park et al, 2018;Park et al, 2019), and hyperosmoticity-induced dry eye (Li H. et al, 2020).…”
Section: Astaxanthin Inhibits Peripheral Inflammationmentioning
confidence: 99%
“…It produced PEG-6HF in 10 mM HEPES pH 7.4 solution at 37 °C for 6 hours, mimicking the biological environment. A sufficient number of samples were collected every hour, and the changes were constantly monitored using a UV-Vis spectrophotometer (Charoensit et al, 2019;Liu et al, 2020). The percentages of the degradation 6HF were calculated based on the initial absorbance of both samples.…”
Section: Resultsmentioning
confidence: 99%